Religious Tolerance of Society in Pati, Central Java: As a Person, Community, and Humanity - Moh Muhtador; Ulya Rofiqoh; Fahrur Rozi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
This article highlights the patterns of tolerance behavior among religious communities in Ngablak Village, Cluwak Sub-district, Pati District, as reflected in the practices of individual, social, and communal life. Individual awareness within a multi-religious and multicultural society constitutes the fundamental capital in constructing human attitudes and behavior. This article aims to identify the characteristics and foundations of society in practicing religious tolerance, as manifested in human attitudes and behavior, so that tolerance emerges regardless of religious background. This study is field research employing a qualitative approach. Data were collected through observation, interviews, and documentation. Interviews were conducted with religious and community leaders in Ngablak Village and analyzed using Gadamer’s historical hermeneutic model. The results indicate that the fundamental capital of society in building religious tolerance is grounded in communal (social) awareness, religious awareness, and humanitarian awareness. Religious tolerance cannot be assessed solely from a religious perspective; rather, historical context and human values also play a significant role in shaping tolerant behavior.